A Comprehensive Network Pharmacology Study on the Diabetes-Fighting Capabilities of Yacon Leaf Extract - Wawo, Arsianita Ester; Simbala, Herny Emma Inonta; Fatimawali, Fatimawali; Tallei, Trina Ekawati (Heca Sentra Analitika, 2024)
Indonesia ranks fourth in the world for the number of diabetes mellitus (DM) sufferers. DM is a group of metabolic disorders characterized by hyperglycemia due to insulin abnormalities. This research employs Network Pharmacology analysis to examine the target proteins and pharmacological network profiles predicted to be influenced by compounds in the leaves of Smallanthus sonchifolius (yacon) for their anti-diabetic effects. Gas chromatography-mass spectrometry (GC-MS) identified 41 secondary metabolite compounds in yacon leaves, seven of which have a Pa value > 0.5. Compound C28 has the highest Pa value as an insulin promoter, at 0.662. A total of 129 target proteins were found for the secondary metabolite compounds in yacon leaves, and 5,112 target proteins were identified for Type 2 Diabetes Mellitus (T2DM). The intersection analysis between yacon leaves and T2DM revealed 32 common proteins. Network analysis highlighted 10 top proteins: ESR1, PPAR-α, HMGCR, CYP19A1, PPARD, PTP1N, GRIN2B, FYN, AR, and SHBG. Among these, PPAR-α shows great potential and promising prospects as a target for further exploration. Considering several parameters, it can be concluded that PPAR-α is a promising protein and a potential target for new drug candidates for T2DM.